Cancers Related to Immunodeficiencies: Update and Perspectives - Mortaz, Esmaeil; Tabarsi, Payam; Mansouri, Davod; Khosravi, Adnan; Garssen, Johan; Velayati, Aliakbar; Adcock, Ian M. (Frontiers in Immunology, 2016)
The life span of patients with primary and secondary immunodeficiency is increasing due to recent improvements in therapeutic strategies. Whilst, the incidence of primary immunodeficiencies (PIDs) is 1:10.000 births, that of secondary immunodeficiencies is more common and are associated with post transplantation immune dysfunction or with immunosuppressive medication for human immunodeficiency virus (HIV) or with human T-cell lymphotropic virus (HTLV) infection. After infection, malignancy is the most prevalent cause of death in both children and adults with primary immunodeficiency disorders (PIDs). PIDs more often associated with cancer include common variable immunodeficiency (CVID), Wiskott Aldrich syndrome (WAS), ataxia-telangiectasia (AT) and severe combined immunodeficiency (SCID). This suggests that a protective immune response against both infectious non-self (pathogens) and malignant self-challenges (cancer) exist. The increased incidence of cancer has been attributed to defective elimination of altered or "transformed" cells and/or defective immunity towards cancer cells. The concept of abberant immune surveillance occurring in PIDs is supported by evidence in mice and from patients undergoing immunosuppression after transplantation. Here, we discuss the importance of PID defects in the development of malignancies, the current limitations associated with molecular pathogenesis of these diseases and emphasize the need for further knowledge of how specific mutations can modulate the immune system to alter immunosurveillance and thereby play a key role in the etiology of malignancies in PID patients.